JUpiter ICy moons Explorer (JUICE): An ESA mission to orbit Ganymede and to characterise the Jupiter system - Grasset, O; Dougherty, M; Coustenis, A; Bunce, E; Erd, C; Titov, D; Blanc, M; Coates, A; Drossart, P; Fletcher, L; Hussmann, H; Jaumann, R; et al. (2013)
Past exploration of Jupiter's diverse satellite system has forever changed our understanding of the unique environments to be found around gas giants, both in our solar system and beyond. The detailed investigation of three of Jupiter's Galilean satellites (Ganymede, Europa, and Callisto), which are believed to harbour subsurface water oceans, is central to elucidating the conditions for habitability of icy worlds in planetary systems in general. The study of the Jupiter system and the possible existence of habitable environments offer the best opportunity for understanding the origins and formation of the gas giants and their satellite systems. The JUpiter ICy moons Explorer (JUICE) mission, selected by ESA in May 2012 to be the first large mission within the Cosmic Vision Program 2015-2025, will perform detailed investigations of Jupiter and its system in all their inter-relations and complexity with particular emphasis on Ganymede as a planetary body and potential habitat. The investigations of the neighbouring moons, Europa and Callisto, will complete a comparative picture of the Galilean moons and their potential habitability. Here we describe the scientific motivation for this exciting new European-led exploration of the Jupiter system in the context of our current knowledge and future aspirations for exploration, and the paradigm it will bring in the study of giant (exo) planets in general. © 2012 Elsevier Ltd.